2018
DOI: 10.3390/ijerph15071536
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Degradation of Lambda-Cyhalothrin Makes Treated Vegetables Relatively Safe for Consumption

Abstract: Lambda-cyhalothrin (λ-cyhalothrin) is the most commonly used pyrethroid insecticide for vegetable farming in Benin. This insecticide is misused and overused by farmers, and hence may pose health hazards to consumers. We monitored λ-cyhalothrin residues in lettuce and cabbage from farms at the market gates in Cotonou and Parakou using high performance liquid chromatography (HPLC) analysis techniques. These residues were also monitored on samples directly from farms (on-farm sampling) for 14 days post-treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…BS: Breeding site; ND: Not detected. www.nature.com/scientificreports www.nature.com/scientificreports/ type 2 pyrethroid used in vegetable farms around these areas 41 . Therefore, there is every possibility that An.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BS: Breeding site; ND: Not detected. www.nature.com/scientificreports www.nature.com/scientificreports/ type 2 pyrethroid used in vegetable farms around these areas 41 . Therefore, there is every possibility that An.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of lambda-cyhalothrin residues in only 2 out of the 12 breeding sites at Houeyiho might be due to its rapid degradation by natural metabolism such as via aquatic organisms residing in breeding sites [47][48][49] . Another degradation pathway could be exposure to sunlight (photodegradation), which has also been highlighted in the pyrethroid degradation process 41 . Djouaka et al 41 reported how λ-cyhalothrin degrades rapidly under UV light, especially at the concentrations used by vegetable farmers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After dermal application of LCH at the dose of 0.25 mg/kg, elimination t 1/2 is 11.2 h [ 16 ]. Traces of LCH are detected in oregano [ 21 ], prunes [ 22 ], and cabbage [ 23 ]. In Poland, large amounts of LCH are used in potato, wheat, and maize cultivation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%